2016
DOI: 10.3389/fpsyg.2016.01693
|View full text |Cite
|
Sign up to set email alerts
|

Neural Correlates of Learning from Induced Insight: A Case for Reward-Based Episodic Encoding

Abstract: Experiencing insight when solving problems can improve memory formation for both the problem and its solution. The underlying neural processes involved in this kind of learning are, however, thus far insufficiently understood. Here, we conceptualized insight as the sudden understanding of a novel relationship between known stimuli that fits into existing knowledge and is accompanied by a positive emotional response. Hence, insight is thought to comprise associative novelty, schema congruency, and intrinsic rew… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
78
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 66 publications
(85 citation statements)
references
References 69 publications
(120 reference statements)
3
78
0
4
Order By: Relevance
“…Although the observed cluster in the left hippocampal gyrus did not reach significance in the whole-brain analysis, the ROI-based analysis suggests that solutions accompanied with AHA! experience exhibit increased hippocampal activity as had been shown before for insight problems during solution (Jung-Beeman et al, 2004;Kizilirmak et al, 2016;Luo & Niki, 2003;Zhao et al, 2013). This hippocampal activation has been associated with detecting novel associations in a problem solving context (Kizilirmak et al, 2016;Luo & Niki, 2003) but it is widely recognized for its role in memory retrieval in general (e.g., Carr, Jadhav, & Frank, 2011;Ranganath, Cohen, Dam, & D'Esposito, 2004).…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…Although the observed cluster in the left hippocampal gyrus did not reach significance in the whole-brain analysis, the ROI-based analysis suggests that solutions accompanied with AHA! experience exhibit increased hippocampal activity as had been shown before for insight problems during solution (Jung-Beeman et al, 2004;Kizilirmak et al, 2016;Luo & Niki, 2003;Zhao et al, 2013). This hippocampal activation has been associated with detecting novel associations in a problem solving context (Kizilirmak et al, 2016;Luo & Niki, 2003) but it is widely recognized for its role in memory retrieval in general (e.g., Carr, Jadhav, & Frank, 2011;Ranganath, Cohen, Dam, & D'Esposito, 2004).…”
Section: Discussionmentioning
confidence: 61%
“…in insight problems (see Shen, 2018 for a meta-analysis). Increased activations in the medial temporal lobe (amygdala, hippocampus, and parahippocampal gyrus) (Jung-Beeman et al, 2004;Kizilirmak, Thuerich, Folta-Schoofs, Schott, & Richardson-Klavehn, 2016;Ludmer, Dudai, & Rubin, 2011;Zhao et al, 2013) and right anterior superior temporal gyrus (Jung-Beeman et al, 2004;Tik et al, 2018) amongst other areas have been reported in solutions with compared to without AHA! experience.…”
Section: Neural Basis For the Aha! Experiencementioning
confidence: 99%
See 1 more Smart Citation
“…Subtle activation changes, not exceeding strict statistical thresholds, were reported in subcortical areas such as bilateral hippocampi, parahippocampal gyri, and anterior and posterior cingulate cortex (Subramaniam, Kounios, Parrish, & Jung‐Beeman, ; Zhao et al, ). Furthermore, in a recent study, Kizilirmak et al () found left hippocampal and parahippocampal activation during insight, though not surviving a strict threshold, and a significant activation in the anterior cingulate cortex (ACC). Additionally, event‐related potentials indicate that the ACC as well as the parahippocampal gyrus are involved in insightful problem solving (Mai, Luo, Wu, & Luo, ; Qiu & Zhang, ).…”
Section: Introductionmentioning
confidence: 98%
“…Due to its mystical phenomenology, 20th century psychologists started to get to the bottom of this observation first coined by the famous psychologist Karl B€ uhler (B€ uhler, 1907). Since then insightful problem solving has been associated with many different cognitive and affective processes as memory, enforcement learning, and emotion (Kizilirmak, Thuerich, Folta-Schoofs, Schott, & Richardson-Klavehn, 2016a;Milivojevic, Vicente-Grabovetsky, & Doeller, 2015;Shen et al, 2016;Webb, Little, & Cropper, 2017). Despite the importance of the Aha!-experience in obtaining creative and insightful solutions and the large corpus of behavioral evidence, imaging studies on the brain mechanisms involved in this phenomenon just emerged recently.…”
Section: Introductionmentioning
confidence: 99%